Assessment of Tear Film Parameters in Smokers and Subjects with a High Body Mass Index - Fagehi, Raied; El-Hiti, Gamal A; Almojalli, Abdullah; Alzuhairi, Faisal S; Alanazi, Mana A; Masmali, Ali M; Almubrad, Turki (Optometry and vision science, 2022)
The current study compares the ocular tear film parameters in three different groups using a single noninvasive, practical, and easy-to-use tool. This study aimed to assess the tear film in smokers, those with a high body mass index (BMI), and healthy subjects using the EASYTEAR view+. Thirty men with a high BMI (>25 kg/m2; 24.4 ± 6.4 years), 30 smokers (25.1 ± 6.1 years), and 30 healthy subjects (22.2 ± 3.5 years) were recruited. Each subject completed the Ocular Surface Disease Index, followed by the assessment of noninvasive tear breakup time, tear meniscus height (TMH), and lipid layer patterns (LLPs). Significant differences were found in the median TMH scores between smokers and healthy subjects (P = .03) and between subjects with a high BMI and the healthy ones (P = .04). The median LLP score was significantly (P < .001) higher in normal subjects (4.0 [1.0]) than in smokers (2.4 [1.0]) and subjects with high BMI (2.0 [1.3]). For subjects with a high BMI, the noninvasive tear breakup time score was strongly correlated (Spearman rank correlation coefficient; r) with TMH (r = 0.552, P = .002) and LLP (r = 0.555, P = .001). The LLP showed that grade B (lipid layer thickness, 30 to 50 nm; more compact) was common in subjects with a high BMI, grade C (50 to 80 nm, gray waves) was predominant in smokers, and grade D (~80 nm, dense white-blue layer) represented the majority of normal eye subjects. Smokers and individuals with a high BMI showed significantly lower lipid layer grades and tear meniscus height scores compared with the control group. The assessment of tear film parameters using the EASYTEAR view+ supports the findings of previous studies that implicate smoking and high BMI as risk factors for dry eye.